2017
DOI: 10.3892/etm.2017.5347
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on preventing mechanical phlebitis arising from indwelling needles in intravenous therapy by external application of mirabilite

Abstract: Various types of complications arising from intravenous indwelling needles have become a challenge in clinical care. It is urgent to seek a simple and cost-effective method for prevention and treatment of phlebitis. We investigated the roles of mirabilite in preventing and treating phlebitis caused by intravenous indwelling needles and provide guidance for prevention and treatment of mechanical phlebitis caused by intravenous indwelling needles. A total of 57 healthy congeneric big-eared New Zealand rabbits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
9
1
1
Order By: Relevance
“…Some Chinese scholars show that by inhibiting the reticuloendothelial system, mirabilite has a positive effect on anti-inflammation. Lu et al's [ 23 ] study in rabbits shows that mirabilite can significantly decrease the expression of IL-1, IL-6, TNF- α, and the severity of inflammatory responses. Wang et al's study shows that, for severe acute pancreatitis patients, the group that used hot compresses with mirabilite takes a shorter time for abdominal distension, abdominal pain, and blood and urinary amylase values to normalize and get the lower level of white blood cell count, C-reactive protein, and interleukin-6 level than the group with conventional nursing care and therapy, which may be due to the anti-inflammatory effects of mirabilite [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some Chinese scholars show that by inhibiting the reticuloendothelial system, mirabilite has a positive effect on anti-inflammation. Lu et al's [ 23 ] study in rabbits shows that mirabilite can significantly decrease the expression of IL-1, IL-6, TNF- α, and the severity of inflammatory responses. Wang et al's study shows that, for severe acute pancreatitis patients, the group that used hot compresses with mirabilite takes a shorter time for abdominal distension, abdominal pain, and blood and urinary amylase values to normalize and get the lower level of white blood cell count, C-reactive protein, and interleukin-6 level than the group with conventional nursing care and therapy, which may be due to the anti-inflammatory effects of mirabilite [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study also reported that phlebitis is another major factor affecting the success rate of indwelling needles. The Visual Infusion Phlebitis scale was used to evaluate patients with phlebitis [8,9] . Most patients reported grade 1 phlebitis, where they experienced slight pain or redness around the intravenous injection site, while a few reported grade 2 phlebitis, which was characterized by pain, redness, and swelling at the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…Serious complications, such as deep venous thrombosis and sepsis, can also arise from mechanical phlebitis (10)(11) . The latter stimulates vascular endothelial cells, platelets, and basophils, leading to the release of vascular endothelial growth factor (VEGF) and some inflammatory factors (such as CRP, TNF-α, ET-1) (12) . These inflammatory changes can induce purpura, erythema, and blisters, causing also serious tissue necrosis or ulcers in the skin tissue around the puncture site.…”
Section: Introductionmentioning
confidence: 99%